2003
DOI: 10.1007/s00421-003-0955-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17-day spaceflight on electrically evoked torque and cross-sectional area of the human triceps surae

Abstract: The effects of spaceflight on triceps surae muscle torque and cross-sectional area (CSA) were investigated on four astronauts using electrically evoked contractions to by-pass neural control. Muscle twitch characteristics, ankle joint angle-twitch torque relation, frequency-torque relation, tetanic torque and fatigability were assessed before, during and after a 17-day Space Shuttle flight (STS-78). Muscle plus bone cross-sectional area (CSAm+b) was evaluated before and after the flight. Whereas no changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
3
35
2
1
Order By: Relevance
“…Interestingly, in the same crew members, neither electrically evoked contractile force assessed in-flight (Narici et al 2003) nor in vivo voluntary strength measured upon landing ) decreased despite triceps surae muscle atrophy (LeBlanc et al 2000). These data are in frank contrast to the present results, which do suggest that MVC decreases as a consequence of the absence of weight bearing accompanied by muscle protein loss.…”
Section: Musclecontrasting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, in the same crew members, neither electrically evoked contractile force assessed in-flight (Narici et al 2003) nor in vivo voluntary strength measured upon landing ) decreased despite triceps surae muscle atrophy (LeBlanc et al 2000). These data are in frank contrast to the present results, which do suggest that MVC decreases as a consequence of the absence of weight bearing accompanied by muscle protein loss.…”
Section: Musclecontrasting
confidence: 81%
“…In addition, crosssectional area of knee extensor and flexor as well as gluteal muscles was measured pre-and post-flight. In the same crew, investigators have previously reported no decrease in electrically evoked contractile force during the flight (Narici et al 2003), or in-vivo plantar flexor strength or fiber size ) upon landing. Since the astronauts were subjected to extensive and frequent in-flight muscle function testing involving the plantar flexors, it has been suggested this may have served as a ''resistance training countermeasure to attenuate whole muscle strength loss''.…”
Section: Introductionmentioning
confidence: 88%
“…However, many other studies in rats (Gardetto et al 1989) and in humans (Larsson et al 1996;Narici et al 2003;Widrick et al 1999) showed that specific tension (i.e., force per CSA) of single fibers (Gardetto et al 1989;Larsson et al 1996;Widrick et al 1999) or whole muscle (Narici et al 2003) can also be reduced following hindlimb suspension (Gardetto et al 1989), bed-rest (Larsson et al 1996) or spaceflight (Narici et al 2003;Widrick et al 1999) experiments. Muscle damage (Narici et al 2003) and/or a decreased number of force-generating cross-bridges (Gardetto et al 1989;Larsson et al 1996;Widrick et al 1999) are classically proposed to explain this latter alteration. It can therefore be conjectured that the decrement in strength induced by the present immobilization treatment could be partially ascribed to muscular changes (i.e., muscular atrophy or specific tension decrement), although this was not directly quantified.…”
Section: Discussionmentioning
confidence: 97%
“…A spaceXight study supports this suggestion. It has been observed that 17 days of spaceXight resulted in signiWcant changes in muscle function during the recovery phase and not in microgravity (Narici et al 2003). Furthermore, unloading has been shown to increase the vulnerability to injury from ECC exercise.…”
Section: Discussionmentioning
confidence: 98%